The Implementation of Hand-Puppets as a Storytelling Media To The Studentsâ Language Skills and Characters (An R&D on the Second Grader of Sdn 6 Karangasem Batang Central Java Indonesia) - Sulianto, Joko; Yulianti, Fitri (Proceeding of International Conference on Teacher Training and Education, 2016)
Teaching bahasa to elementary school students has important role in building attitudes, habits, and basic abilities to develop their language skills.Â  Story telling is a part of it. The story teller must have good performance of voice, intonation, and mimic, so that the listeners can understand and enjoy the performance. The story tellers must be supported by appropriate media; they are hand puppets.Â  The objective of this study is to know the implementation of hand-puppets as a story telling media to support studentsâ language skills and character building of the second graders of SDN 6 Karangasem Batang.Â  It is an R and D research. The data were collected by observing, interviewing teacher, giving tests, and taking documentations. Based on the data, hand-puppets can be used to increase studentsâ language skills in retelling story. Those data were shown by studentsâ active participation during the learning process and their interest, enthusiasm, and brave in retelling story in front of their classmates.Â  There were 10 students who joined in retelling story activity actively in âPembelajaran Iâ. The numbers of students were increased in âPembelajaran IIâ; there were 17 students. The media can also be used as an alternative teaching media to build studentsâ positive characters that made them easily understand and catch the moral value of each story. The researchers suggest to the teachers to create some more interesting media that make the students more fun and interested in joining the learning process.